Eigenschaften von extrudierten Holz-Kunststoff-Werkstoffen auf Basis von Refiner-(TMP-)Fasern und Hanffasern - Schirp, Anke; Stender, Jan (European journal of wood and wood products, 2010)
At present, wood particles (wood flour) with a low aspect ratio are mostly used as fillers in wood-plastic composites (WPC). Reinforcement of WPC and improved strength properties may be achieved by using real wood fibres with a high aspect ratio. WPC based on 70% (wt.) refiner (TMP) wood fibres and mechanically processed hemp fibres were extruded in a two-step process. Eleven compounds based on the two natural fibre types were prepared using a thermokinetic mixer and extruded in a conical, counter-rotating twin-screw extruder. Additional formulation components were polypropylene fibres, maleic anhydride-modified polypropylene (MAPP) and lubricant. It was determined that compounding in a thermokinetic mixer is a useful step for processing of WPC with refiner and hemp fibres as little fibre damage occurred. However, during extrusion, both natural fibre types were severely shortened due to strong shear forces, and homogeneous dispersion of fibres in the matrix was not achieved. WPC based on hemp fibres displayed the best strength properties of the formulations tested. Current extruder screw and die configurations need to be modified to achieve improved fibre reinforcement and to create new, structurally demanding applications for WPC.